Peran Moderasi ukuran perusahaan pada Determinan Agresivitas Pajak pada Perusahaan Manufaktur yang Terdaftar di BEI - Ummi Elsa Rosa; Masta Sembiring (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted with the aim of testing and analyzing the effect of profitability and leverage on tax aggressiveness moderated by company size partially or moderately. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange, while the sample that met the sampling criteria for observations was carried out for five years and there were thirty-three manufacturing companies listed on the Indonesia Stock Exchange. This research approach uses associative research. The data collection technique in this research uses documentation techniques and the analysis technique used is MRA Interaction analysis. The research results show that profitability has no effect on tax aggressiveness, leverage has no effect on tax aggressiveness, company size does not moderate the effect of profitability on tax aggressiveness and company size does not moderate the effect of leverage on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange.